APPLICATION OF MISTLETOE IN CANCER TREATMENT - Haluzinska, Yuliia; Baranovsky, Mikhail (Proceedings of National Aviation University (archive), 2018)
Objective: natural method of cancer treatment with the help of Viscum AlBum is described in the article. Chemical composition, application of mistletoe in medicine and influence on cell lines (NFS-60 and L-41) are considered. Methods: this article considers a microscopic method based on inhibition and quantification of cancer cell lines. Results and discussions: experiment shows that mistletoe dried and fresh extract (from leaves and steams) is effective against both myeloid cancer cells: mouse ( NFS-60 suspension) and human ( L-41 monolayer ). Inhibition of L-41 myeloid cell occurs, because the values of optical density are no more than 1 due to wave length 590 nm. Inhibition of cancer cell occurs, the values of optical density are no more than 0, 1 due to wave length 570nm.